Axisymmetric fluid-dominated wave in fluid-filled plastic pipes: Loading effects of surrounding elastic medium. (15th January 2017) - Gao, Yan; Liu, Yuyou; Muggleton, Jennifer M.
Abstract: Axisymmetric ( n = 0) waves that propagate at low frequencies are of practical interest in the application of acoustic techniques for the detection of leaks in fluid-filled pipelines. A general expression for the fluid-dominated ( s = 1) wavenumber is presented in a thin-walled fluid-filled pipe surrounded by an elastic medium. In this paper the analysis is extended to investigate the loading effects of surrounding medium on the low-frequency propagation characteristics of the s = 1 wave. The analytical model is subsequently applied to MDPE water pipes surrounding by three media, namely an air, water and soil. It is used to demonstrate explicitly the loading effects of surrounding medium, acting as a combination of mass, stiffness and radiation damping on the s = 1 wavenumber. Good agreement is achieved between the measurements and predictions. The theory with experimental validations provides the basis for improving acoustic leak detection methods in fluid-filled pipe systems.